The Link between Engagement and Service Performance: The Mediation Role of Job Satisfaction and Customer-Oriented Behavior - Mohammed A. Sadiq; Arie Indra Gunawan; Adila Sosianika; Fatya Alty Amalia (Politeknik Negeri Bandung, 2022)
This study investigates the impact of engagement on service performance, both directly and through the mediation role of job satisfaction and customer-oriented behavior, among Small-Medium Enterprises (SMEs) frontline employees. 451 frontline employee data were gathered from SMEs in the greater Bandung region, Indonesia. To examine the hypothesized relationship between variables, the data were assessed using Partial Least Square (PLS). Also, the Bootstrap method was employed to assess job satisfaction and customer-oriented behaviors’ mediation role. The result reinforces the existence of a multi-dimensional engagement concept that encompasses the engagement towards both job and organization. This engagement does not directly influence employee service performance; it is influenced indirectly through job satisfaction and customer-oriented behavior. The managerial practices and theoretical significance of these findings are examined.